Telaah Memaknai Penyertaan Allah Dalam Bingkai Teologi Pentakosta - Kosma Manurung (Sekolah Tinggi Teologi Anugrah Indonesia, 2021)
Pentecostals are people who build their understanding of faith on the basis of a practical life that conforms to the Bible. The Bible gives an illustration of God's desire to be with believers. Immanuel is a term that refers to the existence of God who accompanies His people and is manifested by the presence of the Lord Jesus Himself (Matt. 123). This article's research specifically wants to highlight how Pentecostal theology interprets God's inclusion. The method used in this research is descriptive and literature review. How the inclusion of God in the lives of people whom the Bible believes in is discussed in such depth as the inclusion of God in the lives of Joseph, Moses, and Daniel. This article also discusses the real form of God's participation in the person and ministry of the Lord Jesus the gospel. The research results show that God's participation is the desire of God's heart to be present in the daily lives of believers as His chosen people. The presence of Allah also means God's care and protection. An understanding of God's presence awakens faith to believe confidently and live for God.Keywords: immanuel; god inclusion; pentecost; pentecostalism; pentecostal theology AbstrakKaum Pentakosta adalah kaum yang membangun pemahaman iman mereka berdasarkan kehidupan praktis yang menyesuaikan dengan Alkitab. Alkitab memberikan gambaran tentang kerinduan Allah untuk menyertai orang percaya. Imanuel merupakan sebutan yang mengacu pada keberadaan Allah yang menyertai umat-Nya dan di wujud nyatakan oleh kehadiran Tuhan Yesus sendiri (Mat. 123). Penelitian artikel ini secara khusus ingin menyoroti bagaimana teologi Pentakosta memaknai penyertaan Allah. Metode yang digunakan dalam penelitian ini adalah deskriptif dan kajian literatur. Bagaimana penyertaan Allah dalam kehidupan orang percaya yang dicatat oleh Alkitab diulas secara mendalam seperti penyertaan Allah dalam kehidupan Yusuf, Musa, dan Daniel. Artikel ini juga mengulas wujud nyata penyertaan Allah dalam diri dan pelayanan Tuhan Yesus yang dicatat Injil. Hasil penelitian memaparkan bahwa penyertaan Allah merupakan kerinduan hati Allah untuk hadir dalam keseharian hidup orang percaya sebagai umat pilihan-Nya. Penyertaan Allah juga berarti pemeliharaan Allah dan perlindungan Allah. Pemahaman akan penyertaan Allah ini membangkitkan iman untuk dengan yakin mempercayai dan hidup bagi Allah. Kata Kunci: imanuel; penyertaan allah; pentakosta; pentakostalisme; teologi pentakosta